The Role of Consumer Hedonic Behavior in Mediating the Influence of Website Quality and Environment on Impulsive Buying (A Study of Tokopedia Users in Palangka Raya) - Peridawaty Peridawaty; Gema Borneo Poetra; Pratiwi Hamzah; Rian Sidiq Prakoso (Journal of Economic Education and Entrepreneurship Studies, 2026)
The purpose of this study is to test and explain the influence of website quality and the environment on consumer hedonic behavior and impulsive buying on Tokopedia. This study uses a quantitative (positivist) approach; data collection was carried out using a questionnaire. The sample size was determined using the Slovin formula and obtained 196 samples. The sampling technique was random sampling. Respondents in this study were people who had shopped at Tokopedia; respondents were selected as samples. The data analysis method in hypothesis testing was Partial Least Squares (PLS). The results of the study indicate that website quality and the environment directly influence consumer hedonic behavior and impulsive buying on Tokopedia. Likewise, consumer hedonic behavior influences impulsive buying. Consumer hedonic behavior is not a moderating variable in the relationship between website quality and its influence on impulsive buying. The practical implications of this study can provide knowledge and understanding for the public regarding the role of website quality and the environment in efforts to increase sales volume. The limitations of this study lie in the limited research object of people who shop through the website. Thus, the results of the study can only be generalized to the internet user community. The originality of this research provides a basis for model development and proves an integrated conceptual model of the relationship between the influence of website quality and the environment on consumer hedonic behavior and impulsive buying on Tokopedia.